Numerical And Experimental Investigations Of 2d Membrane Airfoil Performance - Abdul Aziz, Mohd Sharizal (2012)

(untitled)
The characteristic feature of a mammalian flight is the use of thin compliant wings as the lifting surface. This unique feature of flexible membrane wings found in flying mammals such as bats and flying squirrel was studied in order to explore its possibility as flexible membrane wings in aerodynamics performance study. The unsteady aspects of the fluid-structure interaction of membrane wings are very complicated and therefore did not receive much attention compared to the rigid wing. Motivated by this, a membrane airfoil consisting of latex sheet mounted on a NACA 643-218 airfoil frame was developed to study effect of membrane flexibility on laminar separation bubble (LSB), effects of membrane thickness, Reynolds number (Re), and membrane rigidity on the aerodynamic performance (lift and drag), meant for low Re applications. Unsteady, two dimensional (2D) simulations were also carried out on rigid and membrane airfoils with the air flow modeled as Laminar and the turbulent cases being modeled using Spalart-Allmaras viscous model. FLUENT 6.3 was employed to study the fluid flow behavior, whereas ABAQUS 6.8-1 was utilized as structural solver, both of which were coupled in real time using the MpCCI 3.1 software. It has been established that, the LSB is greatly influenced by the membrane flexibility, and the membrane airfoil has superior flow separation characteristics over rigid one. Besides that, the effects of skin thickness and Re on the aerodynamic performance are investigated. In general, it was observed that, as the membrane thickness decreases, the lift increases and drag decreases, thereby improving the aerodynamic performance; with similar observation reported for the xvii case with increase in Re. Moreover, using experiment, the studies on the effect of ribs on aerodynamic performances were also presented. The results showed that the rigidity of the membrane skins could significantly affect the performance of the membrane airfoils; as the number of rigid ribs decreases, the lift increases and drag decreases. Finally, the displacement and stress of membrane airfoil with incoming flow has been studied by simulation technique. It was found that the membrane airfoils have deformed by the incoming flow and the Von Mises stress was found fluctuating around the membrane airfoil. The current simulation techniques were also validated by suitable wind tunnel experiments and close agreement was obtained.